2019
DOI: 10.5194/isprs-archives-xlii-4-w12-139-2019
|View full text |Cite
|
Sign up to set email alerts
|

Using the Sleuth Urban Growth Model Coupled With a Gis to Simulate and Predict the Future Urban Expansion of Casablanca Region, Morocco

Abstract: The rapid and sometimes uncontrolled acceleration of urban growth, particularly in developing countries, places increasing pressure on environment and urban population well-being, making it a primary concern for managers. In Casablanca city, Morocco's economic capital, the rapid urbanization was a result of population explosion, rural exodus and the emergence of new urban centers. Therefore, a system for urban growth simulation and prediction to anticipate infrastructural needs became indispensable to optimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…A proper urban growth monitoring comes in handy to urban planners by helping them control development in a sustainable way. With advances in technology such as remote sensing and Geographic Information Systems (GIS) [4], new horizons for analyzing spatiotemporal alterations of Land Use Land Cover (LULC) on a regional and global scale [5], urban/regional planning [6], [7] and the analysis of urban evolution through the implementation of specific models [8] can be carried out. In light of that, several urban growth models such as machine learning and statistical methods, cellular automata-based methods,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A proper urban growth monitoring comes in handy to urban planners by helping them control development in a sustainable way. With advances in technology such as remote sensing and Geographic Information Systems (GIS) [4], new horizons for analyzing spatiotemporal alterations of Land Use Land Cover (LULC) on a regional and global scale [5], urban/regional planning [6], [7] and the analysis of urban evolution through the implementation of specific models [8] can be carried out. In light of that, several urban growth models such as machine learning and statistical methods, cellular automata-based methods,…”
Section: Introductionmentioning
confidence: 99%
“…The model was first developed and applied to forecast urban sprawl in San Francisco and the Washington/ Baltimore regions [30] but has since been calibrated and applied to model the urban growth of other regions in the United States and the world. Some examples are, California counties [34], [35], Honolulu, Hawaii [38], Gdansk, Poland [39], Chiang Mai, Thailand and Taipei, Taiwan [40], Tijuana, Mexico [41], Alexandria, Egypt [42], Yaounde, Cameroon [43] Sydney, Australia [44] Adana, Turkey [4], Sana'a metropolitan city, Yemen [45], Tainan, Taiwan [46], Casablanca region, Morocco [8], Lisbon and Porto, Portugal [48] and the most recent Jinan City, China [47]. These studies have shown and reaffirmed the importance of combining SLEUTH, GIS and remote sensing in the study of urban growth at different times and places.…”
Section: Introductionmentioning
confidence: 99%
“…A review paper on UGPM by Triantakonstantis and Mountrakis (2012) reported that out of 156 manuscripts by different researchers, almost 83% used the CA model for urban growth predication. The SLEUTH (slope, landuse, exclusion, urban extent, transportation and hillshade) is one commonly used CA-based UGPM with many reported studies (Al-shalabi et al, 2013;Bihamta et al, 2015;Clarke and Gaydos, 1998;Herold et al, 2003;Mallouk et al, 2019;Saxena and Jat, 2019). In the SLEUTH model, urban growth rules are applied on a cell-by-cell within a uniform geographical lattice thus making it highly ideal for spatial growth predictions.…”
Section: Introductionmentioning
confidence: 99%
“…The Landsat data derived urban expansion revealed that all nine studied SEA cities experienced significant spatial urban expansion over the period 1987 to 2017 (Figure 5- 4). Strong radial urban expansion from the city centers is observed for Bandung, Bangkok, Ho Chi Minh, Jakarta, Manila and Medan, whereas the expansion is in the form of scattered patches for Kuala Lumpur and Singapore.…”
Section: Landsat Data Derived Urban Expansionmentioning
confidence: 98%
“…A UGPM review paper by Triantakonstantis and Mountrakis (2012) reported that 83% of 156 manuscripts on urban growth prediction used the CA approach. The SLEUTH (Slope, Landuse, Exclusion, Urban extent, Transportation and Hillshade) is one commonly used CA-based UGPM with many reported studies (Al-shalabi et al 2013;Bihamta et al 2015;Clarke and Gaydos 1998;Herold et al 2003;Mallouk et al 2019;Saxena and Jat 2019).…”
Section: Introduction and Overviewmentioning
confidence: 99%